Modeling of velocity regimens for anaerobic and aerobic power exercises in high-performance swimmers - Issurin, V. G.; Kaufman, L. E.; Tenenbaum, G. (The Journal of Sports Medicine and Physical Fitness, 2001)
BACKGROUND: This study was aimed at investigating the validity and eligibillity of a modeling method to determine velocity regimes of highly intensive swimming exercises. METHODS: The model postulates that swimming velocity regimens, which correspond to the three biomotor components, i.e.: Maximal Anaerobic Power, Anaerobic Capacity, and Aerobic Power, can be predicted by special equations using a 50 m all out swim velocity, and the equation coefficient, which determine swimmer's classification. The swimmers are classified into 12 categories according to pre-determined race distance records, and swimmer's capability level. EXPERIMENTAL DESIGN: comparative field study was used to contrast predicted velocity regimens with observed velocity regimes. SETTINGS: national swimming center at the Wingate Institute for Physical Education. PARTICIPANTS: 22 highly trained swimmers (14 male and 8 female) participated in this study and were examined 1-4 times within a period of two years in totally 162 sessions. INTERVENTIONS: the 50 m all-out trial was performed and three basic velocity regimens were predicted according to the modeling procedure. Three diflerent interval sets were carried out by all the swimmers for validation procedures. The blood lactate (BLA) samples were taken after test completion. RESULTS: The correlations between the observed and predicted velocities within each of the three tests were very strong. The RM-ANOVA with respect to lactic acid concentration revealed that across the three measures (different tests) BLA concentration was significantly higher in male swimmers than in female swimmers, and highest in butterfly followed by breaststroke, backstroke, and freestyle stroke. CONCLUSIONS: The modeling method allows to predict desirable velocity regimes in order to develop the main biomotor components of the swimmers. This procedure is recommended for practice as a non-invasive method for designing desired training regimens.